Studi Kasus Evaluasi Tata Kelola Data Kesehatan Rumah Sakit Surabaya - Chindy Maria Orizani; Siti Nur Qomariah; Deanova Nayla Andini; Zammira Andiah Putri (Journal of Health Management Research, 2026)
Background: The largest producers of clinical and administrative health data are hospitals. There are issues with data integrity and quality when hospitals reuse their health data. These issues increase healthcare costs, lead to mistakes in patient care, and take up a significant amount of time for hospital IT staff to extract and synchronize data. Aims: Hospitals can enhance patient safety, boost health sector research, create policies, safeguard data and information assets, and develop procedures and accountability for data and information management by putting health data governance into practice. Only a few nations, meanwhile, are able to establish health data governance in hospitals. Methods: This study is qualitative research with a single case study. The data was taken from the Private Hospitals in Surabaya from June 2022 until December 2023. We used semi-structured interviews with IT and hospital management. There are 20 people as our interviewees. We used thematic analysis. Data governance domain areas are used in our initial code, and we continue to open coding to find the meaning of the interviewee’s statement. The axial code was performed to get critical problem-related health data in the hospital. Results: . Our problem identification yielded six topics. The topics included missing information, inaccurate information, redundant information, inadequate documentation, problems with data discoverability, and a lack of ethical concern in data access. Next, we mapped the issue to the data governance domain. Conclusion: According to this study, data quality management, metadata management, and data security management were the domain areas most necessary for health data governance.